Odpowiedzi

2010-03-09T19:02:38+01:00
2010-03-09T19:06:47+01:00
1.Przekształć ilorazy
(2x+8):(-2) = -x-4
(a-10):5 = ⅕ a -2
9x-7y-3:3 = 9x-7x-1
(-4z-2t):1/2 = -4z * 2 -2t *2 = -8z-4t
(4w-2+3u):(-1 1/3) = 4w * (-¾) - 2*(-¾) + 3u*(-¾) = -3w + 1½ -2 ¼u
0,6+10y-1:(-0,2) 0,6+10y +5

2.Zapisz w jak najprostszej postaci
2x-(-4-3x) = 2x+4+3x = 5x+4
10-2t(t+1) = 10-2t²-2t
-3(2y+1/3)+4y = -6y-1+4y = -2y -1
-6(1-0,5u)+3u/2 / *2
-12+6u +3u = -12+9u
2(3w-1)-w+2/2 = 6w-2-w+1 = 5w-1
3(a-2b)-5(b-2a) = 3a-6b-5b+10a = 13a-11b
Najlepsza Odpowiedź!
2010-03-09T19:10:50+01:00
1.Przekształć ilorazy
(2x+8):(-2)=-x-4
(a-10):5=1/5a-2
9x-7y-3:3=9x-7y-1
(-4z-2t):1/2=-8z-4t
(4w-2+3u):(-1 1/3)=-3w+3/2-9/4u
0,6+10y-1:(-0,2)=-3-50y+5
2.Zapisz w jak najprostszej postaci
2x-(-4-3x)=5x+4
10-2t(t+1)=10-2tkwadrat-2t
-3(2y+1/3)=4y -10y=1
-6(1-0,5u)+3u/2=-6+41/2u
2(3w-1)-w+2/2=5w-1
3(a-2b)-5(b-2a) =13a-11b